Human development in societal context.[article]. - Huston, Aletha C.; Bentley, Alison C.
Low family socioeconomic position is a net of related conditions-low income, material deprivation, single-parent family structure, low-educational level, minority ethnic group membership, and immigrant status. According to ecological theory, proximal contexts experienced by children, including family, material resources, out of -school- youth experiences, schools, neighborhoods, and peers, are mediators of poverty effects. Developmental timing of exposure to poverty conditions and the processes by which effects occur differ for cognitive and social domains of development. Understanding how context combine and interact is as important as understanding their independent influences. Effects maybe cumulative, but advantages in one context can also ameliorate disadvantages in others. Although research is typically based on unidirectional casual models, the relation between the developing child and the context he or she experiences are reciprocal and transactional.Finally, although income inequality has increased greatly, little is known about the influences of relative poverty and social inequality on human.
Keywords: Poverty; Ecological theory; Children; Policy; Social inequality